A escuta musical no Monismo de Triplo Aspecto - Aguiar, Vinícius Jonas de [UNESP] (2015)
In this research we discuss the role of the neuroscientific and the phenomenological approaches of the musical listening according to the Triple Aspect Monism. We initiate describing those two different approaches of the same activity pointing out that the neuroscience of music provides explanations from a third person perspective of what happens to the brain while the subject listens to music, while composers and music educators focus on how we experience the different ways of listening to music. On one hand, in neuroscientific researches we notice descriptions of musical listening based on simple sound stimulus and, in some recent data, based on parts of music of different styles. In the phenomenological approach, several aspects that influence the way we perceive music are taken into consideration, even though that approach is not based on data about the brain functioning. Aiming to establish a complementarity between those approaches, considering they are both important to understand the musical listening activity, we assume the ontology proposed by the TAM. That ontology considers Nature as composed by three irreducible aspects and, therefore, it becomes clear that each approach on the musical listening is providing descriptions on different aspects that compose the musical phenomenon.